Ong bak 2 [videorecording (DVD)] : the beginning - Prachya Pinkaew, 1962-; Panna Rittikrai, 1961-2014; Techaratanaprasert, Akarapol; Jaa, Tony, 1976- (Magnet Releasing : Distributed by Magnolia Home Entertainment, 2010)
A man born into nobility but raised by criminals is trained in the martial arts and attempts to avenge the deaths of his parents in sixteenth-century Thailand.